Government Policies for Food Sovereignty: Disjunction between Ideality and Reality - Patonangi, Fitrinela; Ilmar, Aminuddin; Irwansyah, Irwansyah; Sakharina, Iin Karita (Hasanuddin Law Review, 2018)
The conceptualizes food security and food sovereignty as fluid and changing discourses that define the problem of hunger. The discursive geohistories of food security and food sovereignty in order to identify oppositions and relationalities between them. I argue that the interpretations of, and relations between, food security and food sovereignty vary by geography and scale, as well as by the conceptual and theoretical differences within the discourses themselves. When and where these discourses develop and emerge is central to understanding their oppositions and convergences. How scale is constructed within particular discourses is also important to understanding how they co-exist relationally or in opposition. Food security and food sovereignty discourses are tied to distinctive political and economic histories, ecologies, and identities at the national and local levels. They are differentially deployed depending upon geographic context and the political economy of development and underdevelopment. Both discourses are dynamic and changing in relation to the wider political and cultural economies of food system dynamics across scale. Uniform definitions of each term should be resisted. The point is to understand the geographies of their relational overlap and their continual difference.